The birds of the republic of colombia: (addenda and corrigenda) (1952)
Since 1948 when the first part of The Birds of the Republic of Colombia was published new collections have been made in that country with the result that a certain amount of distributional data have come to hand and a considerable number of forms have been taken which previously had not been recorded from Colombia.